Fifteen years of research in mathematics education based on the Theory of Objectification - Castro Fernández, Felipe; Juárez López, José Antonio; Miranda Viramontes, Isaías (IE Revista de Investigación Educativa de la REDIECH, 2024)
The Theory of Objectification (TO) is part of the contemporary sociocultural theories of Mathematics education, so the objective of this article is to describe the trends in research conducted on the basis of TO since it was first outlined in 2006 by its creator Luis Radford and up until the year 2021. According to a qualitative and descriptive approach, we proceeded with the search and retrieval of documentary sources published in Mathematics education journals indexed in Google Scholar, EBSCO, Redalyc, Scopus, Scielo and Web of Science. The results reported here are based on a qualitative content analysis of a purposive sample of 22 documents that were classified into two trends: the “research” one and the “practical-pedagogical” one; the former is the one to which most of the selected papers belong; however, the latter reveals some emerging studies in terms of teaching and learning proposals and experiences. It is concluded that, after more than fifteen years of research based on TO, it has allowed to broaden the knowledge on the teaching-learning of various mathematical objects, as well as on ethical, environmental, geographic and cartographic topics, from a sociocultural perspective.